Assymbiotic nitrogen fixation in some grasses and in Cyperus rotundus by bacteriae of the genus Beijerinckia Derx - Ruschel, Alaides Puppin; Britto, Disce Pinto Pacca de Souza (Pesquisa Agropecuaria Brasileira, 2024)
In a greenhouse experiment, the effect of nitrogen fixing bacteria of the genus Beijerinckia Derx was studied in the rizosphere of the pasture grasses Hyparrhenia rufa (Nees) Stapf, Panicum maximum Jacq., Paspalum notatum Flugge and of Cyperus rotundus L. Numbers of microcolonies of Beijerinckia were counted at four different stages of plant growth. The following conclusions were drawn: 1. Inoculation with Beijerinckia increased the number of these organisms in bare soil as well as on the "rhizoplan" of the grasses. This indicates that inoculation might be praticable under our conditions and with the studied plants. 2. Without inoculation all plants in this experiment increased the number of Beijerinckia in their "rhizoplan", when compared with the checks without plant growth. 3. This effect was still more pronounced in the case of Paspalum notatum, with and without inoculation. 4. The lowest number of Beijerinckia were found in the "rhizoplan" on Hyparrhenia rufa and Cyperus rotundus. These plants showed the highest N-content in the "rhizoplan" soil. 5. Higher N-contents in the aereal parts of Paspalum, however, were found than in those of H. rufa. Inoculated Paspalum plants contained more nitrogen than not inoculated ones. 6. Where the ratio C/N in the "rhizoplan" soil was higher more Beijerinckia were found and N-content of the plants was higher (Paspalum).